2020
DOI: 10.3390/jcm9103134
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 Levels Are Raised in Chronic HCV Patients with Hepatocellular Carcinoma

Abstract: Background: Since emerging evidence suggests a protective role of proprotein convertase subtilisin/kexin type 9 (PCSK9) on hepatitis C virus (HCV) infection, the aim of the present study was to evaluate the correlation between PCSK9 and HCV infection in hepatocellular carcinoma (HCC) patients. Methods: In this retrospective study, PCSK9 levels were evaluated by ELISA, in plasma samples from control (n = 24) and 178 patients diagnosed for HCC, cirrhosis, or chronic hepatitis, either positive or negative for HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…In HIV-infected patients, coinfection with HCV increased plasma PCSK9 levels [ 35 ]. Fasolato et al observed higher plasma PCSK9 in HCV-infected patients than in non-infected controls [ 22 ]. Our study identified elevated PCSK9 levels in serum of patients with chronic HCV compared to non-infected patients without severe liver diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In HIV-infected patients, coinfection with HCV increased plasma PCSK9 levels [ 35 ]. Fasolato et al observed higher plasma PCSK9 in HCV-infected patients than in non-infected controls [ 22 ]. Our study identified elevated PCSK9 levels in serum of patients with chronic HCV compared to non-infected patients without severe liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Serum PCSK9 levels were moreover induced by dietary saturated fat, fructose and cholesterol [ 37 ]. The studies cited above regarding systemic PCSK9 levels in HCV-infected patients used fasting plasma [ 22 , 24 , 35 ]. Fasting serum was obtained from the patients in the current analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was recently consolidated by a retrospective study, which showed that combining DCP and AFP serum levels in NUC-treated HBV Caucasian cirrhotic individuals, represents a potential surveillance strategy for HCC [ 49 ]. Additional candidate biomarkers for HCC in the blood have been suggested, i.e., proprotein convertase subtilisin/kexin type 9 (PCSK9) [ 54 , 55 ], glypican 3 (GPC3), squamous cell carcinoma antigen (SCCA), cytokeratine-19, osteopontin (OPN), Golgi protein-73 (GP73), alpha-L-fucosidase (AFU) [ 56 ], heat shock 70 kD protein (HSP-70) [ 57 ], annexin A2, midkine (MDK), aldo-keto reductase family 1 member B10 (AKR1B10) [ 58 ], and HCC-responsive miRNAs and cell-free DNA (for a more detailed review, see [ 59 ]). However, even if these candidate biomarkers are promising, to date, none of them have been adopted in the current clinical practice, and they need to be externally validated.…”
Section: Fibrosis and Hcc Screening In The Clinics—state Of The Armentioning
confidence: 99%